Epitalon increases telomere length in human cell lines through telomerase upregulation or ALT activity - Al-dulaimi, Sarah; Thomas, Ross; Matta, Sheila; Roberts, Terry (Biogerontology (Dordrecht), 2025)
Epitalon, a naturally occurring tetrapeptide, is known for its anti-aging effects on mammalian cells. This happens through the induction of telomerase enzyme activity, resulting in the extension of telomere length. A strong link exists between telomere length and aging-related diseases. Therefore, telomeres are considered to be one of the biomarkers of aging, and increasing or maintaining telomere length may contribute to healthy aging and longevity. Epitalon has been the subject of several anti-aging studies however, quantitative data on the biomolecular pathway leading to telomere length increase, hTERT mRNA expression, telomerase enzyme activity, and ALT activation have not been extensively studied in different cell types. In this article, the breast cancer cell lines 21NT, BT474, and normal epithelial and fibroblast cells were treated with epitalon then DNA, RNA, and proteins were extracted. qPCR and Immunofluorescence analysis demonstrated dose-dependent telomere length extension in normal cells through hTERT and telomerase upregulation. In cancer cells, significant telomere length extension also occurred through ALT (Alternative Lengthening of Telomeres) activation. Only a minor increase in ALT activity was observed in Normal cells, thereby showing that it was specific to cancer cells. Our data suggests that epitalon can extend telomere length in normal healthy mammalian cells through the upregulation of hTERT mRNA expression and telomerase enzyme activity.